2015
DOI: 10.2217/fvl.15.62
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Influenza Virulence, Pathogenicity and Transmissibility: What do We Know?

Gabriele Neumann

Abstract: Highly pathogenic influenza viruses of the H5N1 subtype have infected more than 600 people since 1997, resulting in the deaths of approximately 60% of those infected. Multiple studies have established the viral hemagglutinin (HA) surface glycoprotein as the major determinant of H5N1 virulence. HA mediates host-specific virus binding to cells, and mutations that allow efficient binding to viral receptors on mammalian cells are critical (although not sufficient) for H5N1 transmissibility among mammals. The viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…Instead, our lab and others have found that the PA segment in the H1N1pdm09 virus contains a number of host-adaptive mutations that determine the activity of vRdRp in mammalian cells [20][21][22]. Additionally, there have been several studies regarding novel H5N1 and H7N9 avian IAVs whose replicative ability and virulence have been linked to mutations in PA in addition to the previously described host adaptive mutations in PB2 [23,24]. Together these studies show that the PA gene segment also plays a major role in the adaptation of avian IAVs to mammals and the emergence of pandemic viruses.…”
Section: Host Adaptive Mutations In Polymerase Proteinsmentioning
confidence: 95%
See 1 more Smart Citation
“…Instead, our lab and others have found that the PA segment in the H1N1pdm09 virus contains a number of host-adaptive mutations that determine the activity of vRdRp in mammalian cells [20][21][22]. Additionally, there have been several studies regarding novel H5N1 and H7N9 avian IAVs whose replicative ability and virulence have been linked to mutations in PA in addition to the previously described host adaptive mutations in PB2 [23,24]. Together these studies show that the PA gene segment also plays a major role in the adaptation of avian IAVs to mammals and the emergence of pandemic viruses.…”
Section: Host Adaptive Mutations In Polymerase Proteinsmentioning
confidence: 95%
“…Additionally, the recent outbreaks of highly pathogenic avian IAVs led to identification of previously unknown host adaptive mutations in PA. Characterization of H5N1 viruses, which have caused severe disease in humans, shows that some of these viruses contain the characteristic mutations E627K and D701N in PB2 [23]. However, detailed analysis of H5N1 viruses also revealed the presence of host adaptive mutations in PA.…”
Section: Contribution Of Mutations In Pa To Host Adaptationmentioning
confidence: 99%
“…Highly Pathogenic Avian Influenza (HPAI) is a highly contagious avian disease, may cause serious economic losses in poultry industry and poses a potential threat to public health (Neumann, 2015). Since the emergence of HPAI virus H5N1 A/goose/Guangdong/1/1996 (GS/GD96) in China in 1996, descendants of this strain continue to spread among avian species and their hemagglutinin (HA) has evolved into multiple distinct phylogenetic clades, subclades and lineages in different geographic locations mainly in Southeast Asia (Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…NS1, PB1-F2, polymerase proteins), the IFN-I response is nonetheless sustained, and its excessive activation during severe illness can lead to increased mortality. Furthermore, during H7N9 and H5N1 severe infections, TGF-β fails to be activated, contributing to increased pathogenicity (69)(70)(71). SARS-CoV-2 stands out from the other β -coronaviruses and influenza A viruses, with a highly perturbed response downstream of Type I IFN signalling, as reflected in the poor balance of measured pro-and anti-inflammatory cytokines (Figures and 4).…”
Section: Discussionmentioning
confidence: 99%